2017
DOI: 10.1590/1519-6984.07016
|View full text |Cite
|
Sign up to set email alerts
|

Perkinsus beihaiensis (Perkinsozoa) in oysters of Bahia State, Brazil

Abstract: This study reports the pathogen Perkinsus beihaiensis in oysters of the genus Crassostrea on the coast of the State of Bahia (Brazil), its prevalence, infection intensity and correlation with salinity. Oysters (n = 240) were collected between October and December 2014 at eight sampling stations between latitudes 13°55'S and 15°42'S. The laboratory procedures included macroscopic analysis, histology, culture in Ray's fluid thioglycollate medium (RFTM), Polymerase Chain Reaction (PCR) and DNA sequencing. PCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
8
1
2
Order By: Relevance
“…In recent years, the prevalence of Perkinsus observed in oysters from different regions of the country has varied considerably and, although the value found in this study (8%) has been lower than that recorded in oysters from that same estuary in 2015 (17.3%) and in oysters from Carnaubeira River in Maranhão (10.6%), the same was higher than the values recorded in oysters from the estuaries of the Rivers Camurupim, in Piauí (5.3%) and Pacoti, in Ceará, in 2009and 2010. In other states of the northeastern region, the prevalence of Perkinsus recorded in the RFTM assays has been higher than the values mentioned above (Luz et al, 2018;Queiroga et al, 2015;Scardua et al, 2017;Silva et al, 2016). In the present study, the infection intensity ranged from very light to light (clams), very light to severe (oysters) and very light to moderate (mussels).…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…In recent years, the prevalence of Perkinsus observed in oysters from different regions of the country has varied considerably and, although the value found in this study (8%) has been lower than that recorded in oysters from that same estuary in 2015 (17.3%) and in oysters from Carnaubeira River in Maranhão (10.6%), the same was higher than the values recorded in oysters from the estuaries of the Rivers Camurupim, in Piauí (5.3%) and Pacoti, in Ceará, in 2009and 2010. In other states of the northeastern region, the prevalence of Perkinsus recorded in the RFTM assays has been higher than the values mentioned above (Luz et al, 2018;Queiroga et al, 2015;Scardua et al, 2017;Silva et al, 2016). In the present study, the infection intensity ranged from very light to light (clams), very light to severe (oysters) and very light to moderate (mussels).…”
Section: Resultscontrasting
confidence: 64%
“…On the other hand, Perkinsus cells were observed phagocytosed in the tissues of Crassostrea gasar, indicating a defense response of the host (Queiroga et al, 2015). Also, recent studies with oysters from Bahia showed that the animals infected with P. beihaiensis presented hemocytes infiltration and tissue disorganization (Luz & Boehs, 2016;Luz et al, 2018). As can be observed, the effects of infection by this pathogen on the host need to be better understood.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…C. rhizophorae was also reported to be infected by Perkinsus sp. in Bahia State (Brandão et al, ), with P. marinus in Paraíba (da Silva et al, ) and in Ceará (Neto, ) and with P. beihaiensis in Ceará (Sabry et al, ) and in Bahia (Luz, Carvalho, Oliveira, & Boehs, ), and by Perkinsus chesapeaki in Ceará (Neto, ). Perkinsus beihaiensis infection in the clam Anomalocardia brasiliana was also reported in Ceará by Ferreira et al ().…”
Section: Introductionmentioning
confidence: 99%